Animal production systems in south-east and east Asia. Potential and challenges for research - Devendra, C. (International Laboratory for Research on Animal Diseases, 1995)
Animal production systems in South-East and east Asia are discussed in the context of their potential and challenges for research to address poverty alleviation, increased food production and food security and environmentally sustainable development. The projected human population increase, rising incomes and changing consumer preferences will accelerate the demand for, and access to food in the future. This will place considerable pressures on the use of natural resources (land, crops and animals). Technological and socio-economic factors are the key elements that will drive components of the animal industries. The region has a